FAKTOR-FAKTOR YANG MEMPENGARUHI PEKERJA KONSTRUKSI MEMILIH SISTEM PEMBAYARAN UPAH KERJA (KASUS PROVINSI SULAWESI TENGAH) - asnudin, andi (Inersia: Jurnal Teknik Sipil, 2021)
In general, there are two types of payment systems for work wages in construction work, the first is the daily wage system based on the number of working days / hours, and the second is the wholesale system based on the volume or type of work. Some information that is often heard in the construction project environment is about problems that arise as a result of the wage system for construction workers. Therefore, this study aims to determine the factors that influence the construction workers in choosing a work wage payment system. Non-parametric approachment is used in the form of descriptive analysis consisting of data reduction carried out by reading interview transcripts, questionnaires responses, and making notes according to the data. Then a summary of the data is made which provides an overview in the form of narrative text and tables. The results showed that the most workers that used the payment of work wages based on the volume of work of 58.84% and those who used working hours or of daily wages were 41.16%. Factors that influence the two payment systems are: First, based on Work Volume, are (1) Additional working hours, (2) Special jobs (Specialists, (3) Remote work locations, (4) High worker productivity, (5) Employee Competence Fulfilled, (6) Experienced more than 2 years, (7) Low risk of material damage. Second, the payment system based on Working Hours are (1) Work experience less than 2 years, (2) Weather conditions, extreme (3) Availability of materials, (4) High wages for workers, (5) Working hours less than 7 hours per day , (6) Difficult mastery of tools, (7) Low labor productivity.